PENINGKATAN KEAKTIFAN BELAJAR SISWA PADA MATERI PAI MELALUI METODE FOCUS GRUP DISCUSSIAN (FGD) DI KELAS XI SMAN 8 KOTA BEKASI - Zhilal Mustadh’afin; Yayat Suharyat (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
This service aims to implement the Focus Group Discussion (FGD) teaching method on PAI material at the high school level. This service uses a qualitative descriptive method which is carried out in class XI, totaling 35 students which is carried out through the preparation, implementation and evaluation stages. The problems faced by students when learning tend to use the lecture method, especially in PAI lessons, students are only listeners without having to express students' opinions, this results in a decrease in student interest and activity when receiving lessons. The results of this service prove that students have empathy during the learning process and can express creativity in explaining material, hone students' confidence in expressing opinions and train students' cohesiveness with other students which makes the method effective. This model can be a stimulus for educators who want to apply the PAI learning method in the classroom.